An investigation of a requirements management tool elements - Zainol, Azida; Mansoor, Sa'ad (2011)
Developing quality software is becoming challenges that required the practitioners to employ appropriate techniques, methodologies and good practices in software engineering.In the Malaysian software industry, the challenges are the practitioners are lack of practicing software engineering especially in the requirements management practices as well as the requirements management tool is not widely facilitated during software project development.In order to encourage them to overcome these problems, this paper attempts to recommend a requirements management tool that embeds the best practices in managing requirements.In addition, this paper aims to investigate the elements of the tool to guarantee that the tool is appropriate for the Malaysian software needs.Then, a comparative study is carried out to search for various available requirements management tools that have those elements.The result shown that, there is no specific tool that has all the elements in order to fit the Malaysian software needs.Therefore, it is essential to develop a requirements management tool that able to assist the software practitioners in developing quality software.